Exploring Compassion-Buying Behavior Among Demographic Segments During COVID-19 - Mishra, Sasmita; Kar, Brajaballav (Indian Journal of Marketing, 2023)
Purpose :Â The pandemic affected disadvantaged service providers, such as street vendors. Different media urged consumers to â€œno bargainâ€ and â€œvocal for localâ€ to alleviate pandemic challenges. The self-interest and value-seeking customer behavior were contextually unsuitable with the fear of infection, reduced time for buying, scarcity, and price fluctuations. Did compassion influence a personâ€™s buying behavior? This research investigated the validity of a compassion buying scale and found its demographic differences.Â Methodology :Â An online, anonymous survey with convenient sampling collected 551 responses during the second wave of the pandemic in Eastern India. The questionnaire sought responses to demographic and compassion buying measures. The compassion buying behavior scale was developed from relevant literature. The reliability and validity measures calculated from the obtained responses were in the acceptable range.Â Findings :Â The results indicated that during the COVID-19 pandemic, people did less compassion buying. Compassion buying indicated a U-shape curve by age and economic status. To enhance the scale, future research can include bargain intent, product characteristics, and psychographic characteristics.Â Practical Implications :Â Given the large informal market, vendor, and workforce in a developing nation like India, compassion buying is probably the key to the recovery and growth of various products and services typically offered by disadvantaged vendors. The role of compassion in consumption requires additional investigation during normal times.Â Originality :Â This study reported preliminary findings on â€œcompassion buyingâ€ as a distinct aspect of consumer psychology, different from altruism. It complements responsible consumption, ethical consumerism, and sustainable development.